Students’ Difficulties in Answering “Structure and Written Expression” TOEFL-like at STKIP PGRI Sidoarjo - Joko Slamet; Sulistyaningsih Sulistyaningsih (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
Abstract. This study was conducted to investigate the types of questions which were difficult in TOEFL-like and to find the students’ difficulties in answering the ‘Structure and Written Expression’ of TOEFL-like. The subjects of this study were the batch 5 students of Master of English Education (S2 MPBI) at STKIP PGRI Sidoarjo who had TOEFL-like test as the placement test in taking master’s degree. This research applied descriptive qualitative method. The instruments were students’ results of the TOEFL-like Test and interview. The data were taken from Longman Complete Course for the TOEFL written by Deborah Phillips (2003). The results show that there are 18 items (45%) categorized ‘difficult’. Meanwhile, there are 22 items (55%) categorized into ‘very difficult’. There are several reasons of students’ difficulties in answering the ‘Structure and Written Expression’ on the TOEFL-like done as the placement test. First, there was no preparation in advance. Second, students lack of vocabulary. Third, the test was considered difficult because the students took the TOEFL-like for the first time. Lastly, there was a limited time provided.Keywords: students’ difficulty, Structure and Written Expression, TOEFL-likeAbstrak. Penelitian ini dilakukan dengan tujuan untuk mengetahui jenis-jenis soal yang sulit dalam TOEFL-like dan untuk mengetahui kesulitan mahasiswa dalam menjawab 'Structure and Written Expression' dari TOEFL-like. Subjek penelitian ini adalah mahasiswa Batch 5 program Magister Pendidikan Bahasa Inggris (S2 MPBI) STKIP PGRI Sidoarjo yang mengikuti tes TOEFL-like sebagai tes penempatan dalam mengambil gelar magister. Penelitian ini menggunakan metode deskriptif kualitatif. Instrumen yang digunakan adalah Tes TOEFL-like dan wawancara. Pengumpulan data diambil dari Longman Complete Course untuk TOEFL yang ditulis oleh Deborah Phillips. Hasil penelitian menunjukkan bahwa terdapat 18 soal (45%) yang dikategorikan 'sulit'. Sementara itu, terdapat 22 soal (55%) yang dikategorikan 'sangat sulit'. Ada beberapa alasan kesulitan mahasiswa dalam menjawab 'Structure and Written Expression' pada TOEFL-like seperti yang dilakukan saat tes penempatan. Pertama, tidak ada persiapan sebelumnya. Kedua, kurangnya penguasaan kosakata. Ketiga, tes dianggap sulit karena mahasiswa baru pertama kali mengikuti TOEFL-like. Terakhir, waktu yang disediakan terbatas.Kata kunci: kesulitan mahasiswa, Structure and Written Expression, TOEFL-like